Arginase Inhibition Reverses Endothelial Dysfunction, Pulmonary Hypertension, and Vascular Stiffness in Transgenic Sickle Cell Mice. (September 2016) - Steppan, Jochen; Tran, Huong T.; Bead, Valeriani R.; Oh, Young Jun; Sikka, Gautam; Bivalacqua, Trinity J.; Burnett, Arthur L.; Berkowitz, Dan E.; Santhanam, Lakshmi
Abstract : BACKGROUND: In sickle cell disease (SCD), hemolysis results in the release and activation of arginase, an enzyme that reciprocally regulates nitric oxide (NO) synthase activity and thus, NO production. Simply supplementing the common substrate L-arginine, however, fails to improve NO bioavailability. In this study, we tested the hypothesis that arginase inhibition would improve NO bioavailability and thereby attenuate systemic and pulmonary vascular endothelial dysfunction in transgenic mice with SCD. METHODS: We studied 5-month-old transgenic sickle cell (SC) mice and age matched wild-type (WT) controls. SC mice were treated with the arginase inhibitor, 2(S)-amino-6-boronohexanoic acid (ABH; approximately 400 μg/d) for 4 weeks or left untreated. RESULTS: Vascular arginase activity was significantly higher at baseline in untreated SC mice compared to WT controls (SC versus WT, 346 ± 69.3 vs 69 ± 17.3 pmol urea/mg protein/minute; P = 0.0043; n = 4–5 animals per group). Treatment with ABH may significantly decrease arginase activity to levels near WT controls (SC + ABH 125.2 ± 17.3 pmol urea/mg protein/minute; P = 0.0213). Aortic strips from untreated SC mice showed decreased NO and increased reactive oxygen species (ROS) production (NO: fluorescence rate 0.76 ± 0.14 vs 1.34 ± 0.17 RFU/s; P = 0.0005 and ROS: fluorescence rate 3.96 ± 1.70 vs 1.63 ± 1.20 RFU/s, P = 0.0039; n = 3– animals per group). SC animals treated with ABH for 4 weeks demonstrated NO (fluorescence rate: 1.16 ± 0.16) and ROS (fluorescence rate: 2.02 ± 0.45) levels comparable with age-matched WT controls ( n = 3– animals per group). The maximal endothelial-dependent vasorelaxation response to acetylcholine was impaired in aortic rings from SC mice compared with WT (57.7% ± 8.4% vs 80.3% ± 11.0%; P = 0.02; n = 6 animals per group). The endothelial-independent response was not different between groups. In SC mice, the right ventricular cardiac output index and end-systolic elastance were similar (4.60 ± 0.51 vs 2.9 ± 0.85 mL/min/100 g and 0.89 ± 0.48 vs 0.58 ± 0.11 mm Hg/μL), whereas the pulmonary vascular resistance index and right ventricular end-systolic pressure were greater (2.9 ± 0.28 vs 5.5 ± 2.0 mm Hg × min/μL/100 g and 18.9 ± 1.1 vs 23.1 ± 4.0 mm Hg; n = 8 animals per group). Pulse wave velocity (a measure of arterial stiffness) was greater in SC mice compared with WT (3.74 ± 0.54 vs 3.25 ± 0.21 m/s; n = 20 animals per group), arginase inhibition for 4 weeks significantly reduced the vascular SC phenotype to one similar to WT animals ( P = 0.0009). CONCLUSIONS: Arginase inhibition improves NO bioavailability and thereby attenuates systemic and pulmonary vascular endothelial dysfunction in transgenic mice with SCD. Therefore, arginase is a potential therapeutic target in the treatment of cardiovascular dysfunction in SCD.